Sorbents Coupled to Solar Light TiO2-Based Photocatalysts for Olive Mill Wastewater Treatment - Andrea Speltini; Federica Maraschi; Michela Sturini; Valentina Caratto; Maurizio Ferretti; Antonella Profumo (International Journal of Photoenergy)
The aim of this work was to couple physical-chemical approaches with photocatalysis to reduce by a simple, inexpensive way the organic load of olive mill wastewater (OMW), mandatorily prior to the final discharge. Before irradiation, different sorbents were tested to remove part of the organic fraction, monitored by measuring chemical oxygen demand (COD) and polyphenols (PP). Different low-cost, safe materials were tested, that is, Y zeolite (ZY), montmorillonite, and sepiolite. Considerable decrease of organic load was obtained, with the highest abatement (40%) provided by ZY (10 g L−1 in 1 : 10 OMW). Use of the three sorbents, in particular ZY, was convenient compared to commercial activated carbons. UV light photocatalytic tests, performed using P25 TiO2 on ZY-treated OMW, yielded quantitative remediation (ca. 90%). Also solar light provided significative results, PP being lowered by 74% and COD by 56%. Sol-gel anatase TiO2 and N-doped anatase TiO2 were also tested, obtaining good results, around -80% PP and -40% COD. Finally, an integrated approach was experimented by ZY-supported anatase TiO2 (TiO2@ZY). This photoreactive sorbent allowed one-pot treatment of OMW significative abatements of PP (-77%) and COD (-39%) with only 1 g L−1 material, under solar light.